Penanganan Petty Corruption Dengan Denda Damai Sebagai Bentuk Keadilan Restoratif - Simeone, Nicholas Gerard Felix; Frans, Mardian Putra (Universitas Widya Gama Malang, 2025)
This paper aims to discuss the legal issue of the application of peace fines in an effort to deal with petty corruption. This issue was born out of the issuance of Circular Letter of the Deputy Special Crimes Prosecutor Number: B-113/F/Fd. 1/05/2010 on Prioritization of Achievements in Handling Corruption Cases, which instructs agencies to prioritize corruption crimes with large losses and to discontinue corruption cases with small amounts, only by returning losses. Petty Corruption is a corrupt practice that refers to a relatively small amount of money and is carried out in the bureaucratic process of small public officials. So that if petty corruption is subject to the applicable positive law, it will cause injustice. This paper aims to provide a concept analysis of the application of peaceful fines in handling petty corruption that prioritizes restorative justice, guarantees justice, benefits and legal certainty and fulfills the principle of proportionality. The legal research conducted is normative juridical research with a conceptual approach and a statutory approach. The result of this research is that the mechanism of peaceful fines in handling petty corruption is a solution to the problems that arise. The application of peaceful fines to the handling of petty corruption provides a new breakthrough in law enforcement in the crime of corruption. With the application of peaceful fines, the sanctions given are in accordance with the principle of proportionality so that justice, benefit and legal certainty are fully fulfilled and prioritize restorative justice.